Influence of nandrolone decanoate administration on serum lipids and liver enzymes in rats - Samieinasab, Mohammad Reza (ARYA Atheroscler, 2015)
BACKGROUND: Anabolic-androgenic steroids have been associated with several side effects range. This experimental study was conducted to evaluate the effects of nandrolone decanoate (ND, an anabolic steroid) on lipid profile and liver enzymes in rats in Iran. METHODS: Forty adult male and female of Wistar strain rats were randomly assigned to four groups of 10 animals each: male control, female control, ND-male treated (15 mg/kg b.w./day), and ND-female treated (15 mg/kg b.w./day). Serum concentrations of total cholesterol (TC), triglycerides (TG), low-density lipoprotein cholesterol (LDL-C) and high-density lipoprotein cholesterol, aspartate aminotransferase (AST), and alanine aminotransferase (ALT) were measured in all studied groups. RESULTS: Treating rats with ND (case group) resulted in a significant elevation of TC (69.4 ± 8.7), TG (101.6 ± 32.9) and ALT (72.2 ± 13.8) and significant reduction of LDL (6.4 ± 2.6) and AST (138.7 ± 19.4) as compared to control group in female rats. ND supplementation (case group) significantly increased TC (64.4 ± 6.2), AST (255.0 ± 32.0), and ALT (84.3 ± 3.8) in comparison with the control group in male rats. CONCLUSION: Overall, our result indicated that the ND use can cause a negative effect on lipid profile and liver enzyme in rats.